ASSESSMENT OF MITOCHONDRIAL REDOX ACTIVITY DURING CRYOPRESERVATION PROCESS OF INDIAN RED JUNGLE FOWL (GALLUS GALLUS MURGHI) SPERM THROUGH MTT REDUCTION ASSAY - B. A. Rakha; M. S. Ansari; S. Akhter; A. Akhter; E. Blesbois; J. S. Moreno (Journal of Animal and Plant Sciences, 2023)
The experiment was conducted to evaluate the metabolic activity through MTT (3[4,5-dimethylthiazol-2-y1]-2,5-diphenyltetrazolium bromide) reduction assay of Indian red jungle fowl sperm during cryopreservation process. In addition, MTT test was compared with sperm motility and viability data. Sperm analysis was made at pre-dilution, post-dilution, post-cooling, post-equilibration and post freeze-thawing stages. Pearson’s correlation coefficient showed significant (P<0.01) positive association of MTT reduction rate with motility (r=0.85) and viability (r=0.84). A significant (P<0.05) decline was observed in motility, viability and metabolic status after each stage of cryopreservation. The highest (P<0.05) stage-specific percent decrease in motility and viability were observed after freeze-thawing. Nevertheless, stage-specific percent decrease in metabolic status differ (P<0.05) after dilution (5.93 ± 0.12), cooling (8.41 ± 0.03), equilibration (19.1 ± 0.04) and freeze-thawing (30.9 ± 0.08). The total decrease in motility, viability and metabolic activity after the complete freeze-thawing cycle were calculated as 56%, 47% and 52%, respectively. It is concluded that MTT reduction assay is simple and reliable method to evaluate mitochondrial redox activity in sperm of this threatened species.
Keywords: Indian red jungle fowl; Metabolic redox activity; MTT Reduction; DNA integrity